-11+4n=5-(11+17)

Simple and best practice solution for -11+4n=5-(11+17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11+4n=5-(11+17) equation:


Simplifying
-11 + 4n = 5 + -1(11 + 17)

Combine like terms: 11 + 17 = 28
-11 + 4n = 5 + -1(28)

Multiply -1 * 28
-11 + 4n = 5 + -28

Combine like terms: 5 + -28 = -23
-11 + 4n = -23

Solving
-11 + 4n = -23

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 4n = -23 + 11

Combine like terms: -11 + 11 = 0
0 + 4n = -23 + 11
4n = -23 + 11

Combine like terms: -23 + 11 = -12
4n = -12

Divide each side by '4'.
n = -3

Simplifying
n = -3

See similar equations:

| (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) | | 6x+-10=110 | | 5x(x^3-x^2-2)=0 | | 20+2.50(19)=x | | 20+2.50(20)=x | | 20+2.50(18)=x | | 20+30+p=180 | | -9.1=k-6.3 | | 20+2.50(17)=x | | 3.2+d=5 | | 5x^2+41x-54=0 | | 20+2.50(16)=x | | 7(n-7)(8n-7)=0 | | 2x-2(x+1)=3 | | 60+19x+5.75x=159 | | -30=j-10+11j | | 3y-6=-2y-6 | | 180-(19x+4)=y | | (4x+3)(3x^2+3x+1)= | | 3m-4=6m | | 1d/2d-3/4=3d/5D | | R=s-5 | | 20+2.50(15)=x | | 10=.25(b-12) | | 12(2x+3)-3(i+7x)=0 | | -3m+5(1+m)=6+2m | | 12t^2-7t+1=0 | | 5x+7-3x=-8+3x | | 55+8x=25 | | -9s+2=-16 |

Equations solver categories